The phenomenon of purchasing second-hand products by the BOP consumers. (November 2020) - Mukherjee, Srabanti; Datta, Biplab; Paul, Justin
Abstract: This study explores the motivations and consequences of purchasing second-hand (SH) products by the rural and sub-urban (RSU) base of the pyramid (BOP) consumers using a qualitative phenomenological approach. This study has also examined the preferred purchase points for buying SH products by the RSU BOP consumers. Findings revealed that the RSU BOP consumers preferred their personal sources over offline and online retails while buying a SH product. The economic motivations, need for fulfilling aspirations, apathy towards cheap brands, need for social recognition, and pester power of school/college going children were found as the motivations behind the purchase of SH products by the RSU BOP consumers. This study has also identified that increasing consumption of branded SH products results in compensatory consumption, increased consumerism, and overwhelming recurring cost at the RSU BOP. This study has put forth a conceptual model leading to a comprehensive understanding of the purchase points, motivations, and consequences of SH purchase by the RSU BOP consumers. It has advanced the social comparison theory and the theory of compensatory consumption in the context of SH buying by BOP consumers. This study would fill the gap in the literature on consumer behaviour and BOP by examining such a novel issue. The practical and social implications of the study have been discussed. Graphical abstract: Image 1 Highlights: This study has explored the motivations, sources and consequences of purchasing SH products by the RSU BOP consumers. This study has put forth a conceptual model showing the purchase points, triggers, and consequences of SH purchase by the RSU BOP consumers. Our study has advanced the social comparison and compensatory consumption theories indicating their implications on the SH buying at the BOP.